Microvascular Decompression using Muscle Graft for Vertebral Artery Medullary Compression Syndrome - Karki, Prasanna; Shah, Damber Bikram; Joshi, Sumit; Poudel, Prakash; Kayastha, Jessica; Sharma, Gopal Raman (Nepal Journal of Neuroscience, 2020)
It is well known that brainstem dysfunction may be caused by vascular compression of the medulla oblongata. However, only a limited number of reports have found microvascular decompression surgery to be an effective treatment for symptomatic patients with medulla oblongata dysfunction. This report describes a patient with vertebral artery compression of lateral medulla oblongata who presented with lateral medullary syndrome. Microvascular decompression surgery using the transcondylar fossa approach was effective in relieving patient symptoms. The transcondylar fossa approach and the transposition of vertebral artery along with autologous muscle graft interposition technique is appropriate in microvascular decompression surgery to relieve vertebral artery compression of medulla oblongata.